Communication Management of the Sidoarjo Deaf Action Community (Aktu) in Resolving Internal Conflict - Hurum Maqshurot Filkhiyam; Nur Maghfirah Aesthetika (Indonesian Journal of Cultural and Community Development, 2021)
The Sidoarjo Deaf Action Community has a vision to introduce Deaf culture and sign language widely in society. The word "Deaf" was chosen because it more presented themselves. In the communication process within the community, deaf members often experience conflicts that have various impacts on the progress of the community. Therefore, good communication management is needed juxtaposed with the application of conflict resolution type management techniques. The type and basis of this research is descriptive qualitative, with the technique of determining the informants using purposive sampling. The result of this research is that the communication process of the AKTU community tends to be informal although in some cases it is also applied formally. Conflicts that occur related to the inactivity of members and the presence of a wrong connection can have a functional or dysfunctional impact. Community communication management helps a lot in resolving internal conflicts, and the AKTU community applies 8 of 9 resolution techniques.